State distribution of new patients presenting with cleft lip and palate to the university college hospital: a pilot study. (2018)
Background: The UCH/Smile Train partnership, which offers free cleft surgeries to patients provides succor. Objective: The objective of the study was to determine the state distribution of new patients presenting with cleft lip and palate, to The UCH. Method: A retrospective review of all new cleft patients presenting to The UCH between January 2012 and June 2015. The data obtained were their local government area of residence, age of the patients, gender of the patients and the type of cleft. Descriptive statistics was used to analyze the distribution of patients seen while Chi square test was used to analyze the influence of gender and laterality on the type of cleft. Results .'Sixty-seven eligible patients were seen within the study period. Majority (83.6%) of patients seen were from 14 of the 33 Local Government Areas (LGA’s) in Oyo state. Patients were seen from LGA’s in proximity to UCH. A few (16.4%) of the patients came from outside the state. Iwajowa, the LGA with the least number of patients (1.8%) was furthest from UCH. Left sided clefts were significantly more than bilateral or right-sided clefts (p=0.001). Most of the patients from Oluyole LGA had CP while no patient with CP was seen from Lagelu and Akinyele LGA’s. Conclusion: There is the need to intensify cleft awareness programs. Further studies into the health habits, cultural beliefs and genetic profile of communities may explain some regional distribution of cleft types seen.